Identification of SARS-CoV-2 RNA in the conjunctival swab of an Italian pediatric patient affected with COVID-19: A case report. Issue 2 (March 2022) - Quaranta, Luciano; Rovida, Francesca; Riva, Ivano; Bruttini, Carlo; Brambilla, Ilaria; Baldanti, Fausto; De Angelis, Giovanni; Marseglia, Gian Luigi
Introduction: To report a case of identification of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) RNA in ocular specimen in a pediatric patient affected with Coronavirus disease 2019 (COVID-19) with no signs of ocular involvement. Case description: A 11-year old male patient with confirmed COVID-19 infection was hospitalized at the Pediatric Clinic Clinic of the IRCCS Foundation and Hospital San Matteo, Pavia, Italy. Three days after hospital admission, because of the patient complaining very mild ocular symptoms, an ophthalmological evaluation was performed. No signs related to conjunctivitis or keratitis were found but a conjunctival swab was collected as well, based on patient's medical history. The specific SARS-CoV-2 reverse transcription PCR (RT-PCR) was performed, unearthing the presence of viral RNA from the swab. On day 25 from hospitalization, the conjunctival swab was repeated, giving negative result. Conclusions: This is the first report of the identification of SARS-CoV-2 RNA in ocular specimen in a pediatric patient without signs of ocular involvement. However, despite the transmission through tears is theoretically possible, it is still unclear whether this could be considered as an important route for the spread of SARS-CoV-2.